2023
DOI: 10.1021/acsami.3c07210
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency of Formaldehyde Removal and Anti-bacterial Capability Realized by a Multi-Scale Micro–Nano Channel Structure in Hybrid Hydrogel Coating Cross-Linked on Microfiber-Based Polyurethane

Abstract: Inspired by the transpiration in the tree stem having a vertical and porous channel structure, high efficiency of formaldehyde removal is realized by the multi-scale micro–nano channel structure in a hybrid P­(AAm/DA)-Ag/MgO hydrogel coating cross-linked on microfiber-based polyurethane. The present multi-scale channel structure is formed by a joint effect of directional freezing and redox polymerization as well as nanoparticles-induced porosity. Due to the large number of vertically aligned channels of microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…As shown in Figure S11, SEM images before and after the degradation of formaldehyde by the coating were observed and compared, and the overall structure of the coating did not change significantly, indicating that light irradiation did not have a significant effect on the coating (Table S1). Summarizes a number of reports of coatings eliminating formaldehyde, further demonstrating the superior performance of the coating in eliminating formaldehyde. The formaldehyde degradation experiment was carried out with 0.1 g of pure photocatalyst, and it could be seen from Figure S12 that it has about 85% of the elimination effect, which indicated that the formaldehyde elimination efficiency was improved after preparation into the coating. To summarize, the coatings were effective for the elimination of formaldehyde…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure S11, SEM images before and after the degradation of formaldehyde by the coating were observed and compared, and the overall structure of the coating did not change significantly, indicating that light irradiation did not have a significant effect on the coating (Table S1). Summarizes a number of reports of coatings eliminating formaldehyde, further demonstrating the superior performance of the coating in eliminating formaldehyde. The formaldehyde degradation experiment was carried out with 0.1 g of pure photocatalyst, and it could be seen from Figure S12 that it has about 85% of the elimination effect, which indicated that the formaldehyde elimination efficiency was improved after preparation into the coating. To summarize, the coatings were effective for the elimination of formaldehyde…”
Section: Resultsmentioning
confidence: 97%
“…In our sequential fabrication process, we achieved a directionally aligned microstructure with pores between layers that varied over 1 order of magnitude from 1 to 10 μm; these variations affected the alignment and layering of the architecture (Figure M). Moreover, the surface of the final product was assessed through SEM-EDS mapping, which showed that PEDOT:PSS was uniformly coated on the PVA matrix (Figure S2, Supporting Information). To compare the effects of directional versus non-directional freezing on the microstructure, we used non-directional freezing in place of the directional freezing-induced alignment process (Figure G).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the increase in the intensity of broad band at 3298 cm –1 shows the intermolecular hydrogen bonding between the –OH groups of silica and castor oil, which proves the encapsulation of oil in silica nanocapsules. Furthermore, to improve the clarity on encapsulation of castor oil in silica nanocapsules, EDAX elemental composition ,,, was carried out for bare silica nanocapsules with vinyl sulfone terminal and oil-loaded silica nanocapsules with a vinyl sulfone terminal. The EDAX elemental composition for silica with vinyl sulfone terminal with and without oil is displayed in Table S2.…”
Section: Resultsmentioning
confidence: 99%